Strategi Segmenting, Targeting, Positioning dalam Pemasaran Global - Khori Ayu Tridyanthi; Aidhawani Aidhawani; Aditya Fadillah; Adinda Sefina Annisa; Suhairi Suhairi (MAMEN: Jurnal Manajemen, 2023)
Generally, if a company wants to get sales from the goods or services they create, it needs a process of marketing activities. Competition in the increasingly tight business world will make it imperative for every company to determine the right policies in order to be able to push the goals and desires of the company. This requires an analysis of the right strategy for the company with the STP strategy which is called segmenting, targeting and positioning. The method used in this study uses the Library Resources method, which is a method used by searching for data sources originating from library research. Segmenting strategies in global marketing by setting segment sizes, growing segments, knowing the costs of using segments, making adjustments, knowing the competitive position. Targeting strategy in global marketing by way of single market concentration, product specialization, selective specialization, total coverage. The stages of developing a positioning strategy by identifying competitive advantages, creating advantages, and evaluating the reaction of the target market.